Komunikasi Orang Tua Terhadap Anak Perempuan Tentang Kesetaraan Gender di Desa Pargarutan Jae Kecamatan Angkola Timur Kabupaten Tapanuli Selatan - Romadona, Syahrul; Sikumbang, Ahmad Tamrin; Harahap, Suheri (Universitas Labuhanbatu, 2023)
This research is motivated by the phenomenon of increasing gender equality for girl in Pargarutan Jae Village. The aim of this research is to determine the communication used by parents towards girls about gender equality and girls' responses to parents' communication about gender equality. This research uses a qualitative method with a descriptive approach. In collecting data, researchers used observation, interview and documentation data collection techniques. The informants in this research were 15 (fifteen) people from 5 (five) families (father, mother and one daughter). The research results obtained are first, related to parents' communication with girls about gender equality, it was found that parents when communicating with girls applied an attitude of openness, empathy, supportiveness, positive attitude and equality. Parents also began to let go of the influence of the patrilineal and rigid Batak Angkola culture on women. Second, related to girls' responses to parental communication about gender equality, it was found that girls felt equality so that they had the same access, participation, control and benefits as boys.